Exploring the Locally Produced Wine to the Tourism Industry in Abulug, Cagayan, Philippines - Bunagan, Jhoanne Rae; Catacutan, Karen Joy; Comonical, Denice Faye; Gamiao, Zhea Charis; Lopez, Christina Ericka; Tolentino, Jean Aidan Pierre (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aimed to explore the contributions, challenges and opportunities of the locally produced wine in Abulug, Cagayan, Philippines. A qualitative research design was used in the study. Results revealed that the Municipality of Abulug had difficulties in promoting the locally produced wine. The study concludes that the findings are more of challenges than contributions to the tourism industry. The researchers recommend to the Local Government of Abulug to conduct feasibility studies, mass production of nipa wine and create design and development of packaging to enhance marketability of the product